IMPROVING THE METHOD FOR DETERMINING THE PHYSIOLOGICAL AND SANITARY POTENTIAL OF GHERKIN SEEDS - Catão, Hugo Cesar Rodrigues Moreira; Castilho, Ítala Menegon; Caixeta, Franciele; Tebaldi, Nilvanira Donizete; Freitas, Pâmela Gomes Nakada [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2021)
Gherkin seeds usually show irregular physiological quality. Seed production requires fast and reliable tests to evaluate seed quality. Germination test is considered a recognized analysis method; however, seed technology has pursuit the improvement of vigor tests aiming the evaluation of seed’s physiological potential. Thus, the objective of this work was to evaluate procedures to perform the test of accelerated aging and determine the physiological and sanitary potential of gherkin seeds. Four seed lots of cultivar Liso Calcuta were used in the study. To evaluate the initial physiological quality the water content was determined and germination and emergence tests, as well as indices of germination speed and emergence speed were used. The accelerated aging test was performed as traditionally and with saturated saline solution, with 48, 72 and 96 hours, at temperatures of 41o C and 45o C. After aging, the water content was determined, and seeds’ germination and sanity tests were performed. The experiment was set under a completely random design in factorial 4x3x2 (lots x aging periods x temperatures). The standard accelerated aging test and the test with saturated saline solution at 41o C for 96 hours were efficient to evaluate the vigor of gherkin seeds. Saturated saline solution provides uniform water absorption and deterioration in gherkin seeds, allowing to discriminate seed lots in different vigor levels. The salinity test after accelerated aging with saline solution reduces the incidence of some fungi.
Keywords: Cucumis anguria; Seed sanity; Seeds quality; Seeds vigor; Vegetable